Finance and Development, June 1978. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1978)
This paper examines the expanded role for the International Finance Corporation (IFC) with a major capital increase. The paper highlights that for the first time in its history, the IFC is undertaking a major increase of its share capital. In a decision made by its Board of Governors in November 1977, the IFC's authorized capital stock has been increased by USD 540 million, from USD 110 million to USD 650 million. Of the increase, USD 480 million has been allocated for subscription by current member countries. More than USD 165 million has already been subscribed and USD 33 million paid.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet